2010
DOI: 10.1007/s11556-010-0073-6
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and maximal physical performance

Abstract: Elite master athletes with long-term devotion to physical training offer an economical means of investigating the effects of ageing and habitual exercise on maximal physical performance. Ideally, individuals with optimised living habits throughout their lives could serve as a human model of 'primary' or 'inherent' ageing, where age-related changes are not confounded by sedentary life-style and associated chronic diseases. A limitation of this approach is the selection bias as those with inherently high physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…2). It has recently been shown that the individual development of muscle plasticity in the elderly makes it possible to modify the age-associated decline even in maximal physical performance at least for some time [89]. The higher aerobic capacity in trained elderly people is related to an increase in the abilities of the cardiovascular system and, to a lesser extent, to an increase in muscle mitochondrial concentration and capacity [73].…”
Section: Endurance Exercise Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…2). It has recently been shown that the individual development of muscle plasticity in the elderly makes it possible to modify the age-associated decline even in maximal physical performance at least for some time [89]. The higher aerobic capacity in trained elderly people is related to an increase in the abilities of the cardiovascular system and, to a lesser extent, to an increase in muscle mitochondrial concentration and capacity [73].…”
Section: Endurance Exercise Trainingmentioning
confidence: 99%
“…Here, the lesser extent means that regular aerobic activity provides a foundation for an increase of muscle oxidative capacity in the elderly. At this point, it is useful to repeat the viewpoint of Suominen [89] that adequate physical performance is an essential element of a healthy and productive life among the elderly. Although factors such as health, physical function, and independence constitute components of the quality of life in the elderly, physiological functioning is significant in determining the ability to maintain independence and an active interaction with the environment [85].…”
Section: Endurance Exercise Trainingmentioning
confidence: 99%
“…Previous studies have precisely characterized age-related changes in maximal physical performances throughout the aging process or even during the entire life span (7)(8)(9)(10)(11)(12)(13). Investigation throughout the entire life span offers the advantage of a complete view of age-related changes, preventing methodological and theoretical misconceptions about the dynamics of aging.…”
mentioning
confidence: 99%
“…This progression was then followed by an exponential decline associated with the aging process (9). Analysis of such a pattern in highly trained athletes represents a unique model for the ideal age-related changes during the normal aging process, without these factors being confounded by concomitant disease, as only the best human performances are taken into account (4,13). In fact, this age-related pattern was found not only at both population and individual levels within highly trained athletes, but also in the general population during both cross-sectional and longitudinal studies in a wide range of physical and cognitive parameters (10,11,14).…”
mentioning
confidence: 99%
“…Physical capacity is inversely proportional to age. 19 Thus in the context of soccer, this relationship may 2 or may not have a negative influence on the technical/tactical performance of referees. 20 Studies have suggested that a slight impairment in physical fitness due to age can be overcome by relevant experience in refereeing, and consequently, does not affect the technical performance of these professionals.…”
Section: Discussionmentioning
confidence: 99%